Analysing Picture Books that Challenge Gender Stereotypes Multimodally - Moya-Guijarro, Jesús; Ventola, Eija (Revija za elementarno izobraževanje, 2023)
This paper identifies the transitivity strategies used in six picture books that aim to challenge gender stereotypes. They were selected because of the large number of commonalities they share; they are all authentic texts, written in English and were not created for experimental purposes. In addition, the selected stories are intended for children (four to nine years old). The theoretical frameworks adopted are SFL (Halliday 2004) and Visual Social Semiotics (Kress and van Leeuwen 2006, Painter et al. 2013). The findings show that the meaning load carried by embedded images (action plus reaction), together with verbal and mental processes of perception, provides essential cues for fostering progressive gender discourses. The analysis also demonstrates that metonymies are essentially used to highlight important aspects of the plot that challenge gender stereotypes.
Keywords: Systemic Functional Linguistics, Visual Social Semiotics, Metonymy, Representational Meaning, Gender Stereotypes in Picture Books